KV 5 : a preliminary report on the excavation of the tomb of the sons of Rameses II in the Valley of the Kings - Weeks, Kent R. (Publications of the Theban Mapping Project ;, 2000)
"The Theban Mapping Project (TMP) was established in 1979 to prepare a detailed survey and archaeological database for the Theban Necropolis. As part of its work in the Valley of the Kings, it relocated KV 5. Clearing that tomb, the TMP discovered that what had been thought to be an unimportant, uninteresting, uninscribed pit tomb was actually the largest tomb ever found in Egypt. KV 5 is known to have 150 corridors and chambers on several levels and many more are likely to be discovered. The tomb is unique in size and plan and in its function as a family mausoleum for many of the sons of the pharaoh Rameses II." "This is the first technical report on KV5. It covers much of the work undertaken between 1988 and 1999. Copiously illustrated, this study is a reference for understanding one of the most important discoveries ever made in the Theban Necropolis."--Jacket.